The Migrant Priests of the Tamil Diaspora Hindu Temples: Caste, Profiles, Circulations and Agency of Transnational Religious Actors - Pierre-Yves Trouillet (South Asia Multidisciplinary Academic Journal)
Many aspects of the contemporary transnationalization of Hinduism have already been well studied, such as long-distance nationalism or the sense of belonging to a transnational community, but very little attention has been paid to the ritual actors who actually circulate within the diaspora space. Based on biographical interviews conducted in two major countries of Hindu immigration (Mauritius and Canada), this article proposes to shed light on the Hindu temple priests who migrate from South India and Northern Sri Lanka to meet the ritual needs of the Tamil diaspora, which is particularly involved in the Hindu temple constructions that have multiplied throughout the world since the 1980–1990s. By focusing on their caste, their migratory profiles, their circulation, and their agency, the article shows that these “migrant priests” actively contribute to shaping the forms that transnational Hinduism takes in different Tamil immigration countries. More broadly, it is argued that it is necessary to pay attention to this type of “circulating” religious actors to fully understand the current stakes, trends, and mechanisms of the transnationalization of Hinduism.